Right to Change Religion in Malaysia - Noor ‘Ashikin, Hamid; Maheran, Makhtar (2014)
A Muslim’s decision to change religion in Malaysia was not an autonomous one. Faiza J opined that if a person were allowed to renounce Islam without obtaining declaration from the religious body, it would create chaos and confusion with the administrative authority managing Islamic affairs, both Muslim and the non-Muslim communities as a whole. The paper attempts to look at the issue of right to change religion in Malaysia by firstly examining the relevant injunctions of the Quran and Sunnah on apostasy and secondly to discuss provisions in the Federal Constitution, especially the effect of article 121(A) of the Federal Constitution in determining the proper jurisdiction of the court to solve these matters. The study is a qualitative research where data collection is done by library research. The data is obtained from related legal provisions, primarily the Federal Constitution, state enactments of Malaysia, the Holy Quran, Sunnah, books, and journals, newspapers’ articles, conference proceedings and Universal Declaration of Human Rights 1948. Having read through the relevant articles on the Constitution, it was found that apostasy, or the right to apostate is not clearly provided for in the Federal Constitution. Finally, this article puts forward some important recommendations to improve the law of apostasy in Malaysia.